Perspectives on data analytics for gaining a competitive advantage in football: Computational approaches to tactics - Olthof, S.; Davis, J. (Science and Medicine in Football, 2025)
The role of data-driven analyses is becoming more prominent in football. These have the potential to impact decision-making processes for team performance and player recruitment. Research in this area makes use of large datasets consisting of event and tracking data from multiple teams, leagues and seasons. A well-known computational solution is the Expected Goal model for post-match analysis and operational decision-making.